2015
DOI: 10.1371/journal.pone.0141764
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Spontaneous Active Motility of Hair Cell Bundles

Abstract: Hair cells of the inner ear exhibit an active process, believed to be crucial for achieving the sensitivity of auditory and vestibular detection. One of the manifestations of the active process is the occurrence of spontaneous hair bundle oscillations in vitro. Hair bundles are coupled by overlying membranes in vivo; hence, explaining the potential role of innate bundle motility in the generation of otoacoustic emissions requires an understanding of the effects of coupling on the active bundle dynamics. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…Hair bundles often exhibited synchronization, despite dispersion in their natural frequencies as large as 5-fold (Fig. 4d-g) [23], consistent with our theoretical predictions for nonisochronous oscillators.…”
Section: Resultssupporting
confidence: 88%
“…Hair bundles often exhibited synchronization, despite dispersion in their natural frequencies as large as 5-fold (Fig. 4d-g) [23], consistent with our theoretical predictions for nonisochronous oscillators.…”
Section: Resultssupporting
confidence: 88%
“…When the membrane depolarizes due to Na + entry from pulsed cholinergic stimuli, both transient and persistent gNa changes contribute to maintaining the voltage gain between pulses because in that voltage range inactivation is inconsequential (h≈1). With a fixed subthreshold background (syn clamp 0.0074 0Hz ) a plot of AP frequency versus 200 Hz stimuli of increasing amplitude generates a “devil’s staircase” plot [ 41 ] Fig 9Bii ). Below the critical pulsatile stimulus amplitude required for any given AP frequency, it would be possible, given a noise-free system, to discern period doubling, tripling etc.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on bullfrog sacculus have also demonstrated multimodal SOAEs at 2:1 and 3:1 ratios of SOAE frequencies (Zhang et al, 2015). Although Zhang et al (2015) report harmonic but not cubic SOAEs, this may reflect the fact that the overlying otolithic membrane was digested, with the result that the hair bundle was free standing. In this condition, there is no bias on the stereocilia in the bullfrog sacculus preparation.…”
Section: Discussionmentioning
confidence: 99%